Apremilast monotherapy for long-term treatment of active psoriatic arthritis in DMARD-naïve patients. (8th June 2021) - Wells, Alvin F; Edwards, Christopher J; Kivitz, Alan J; Bird, Paul; Guerette, Benoit; Delev, Nikolay; Paris, Maria; Teng, Lichen; Aelion, Jacob A
Abstract: Objectives: Apremilast monotherapy was evaluated up to 5 years in PALACE 4 (fourth PsA Long-term Assessment of Clinical Efficacy study) DMARD-naïve patients with PsA. Methods: Patients with active PsA were randomized (1:1:1) to placebo, apremilast 30 mg or apremilast 20 mg twice a day. Placebo patients were rerandomized to apremilast at week 16 or 24. Double-blind apremilast continued to week 52, with a 4-year open-label extension (≤260 weeks of exposure). Analyses through week 260 were based on observed data. Results: A total of 527 patients were treated. Among patients randomized to apremilast 30 mg at baseline, 45.5% completed week 260. At study end, 24.8% reported conventional synthetic DMARD or steroid use for any reason. At week 260, 65.8%/39.0%/20.3% of apremilast 30 mg patients achieved ACR20/ACR50/ACR70 responses, respectively. PsA sign and symptom improvements were sustained up to week 260 with continued treatment, including reductions in swollen (84.8%) and tender (76.4%) joint counts. Among apremilast 30 mg patients with baseline enthesitis or dactylitis, 71.2% achieved a Maastricht Ankylosing Spondylitis Enthesitis Score of 0 and 95.1% achieved a dactylitis count of 0. Over 50% of patients achieved a HAQ Disability Index minimal clinically important difference (≥0.35). In patients with ≥3% baseline psoriasis-involved body surface area, 60.3% and 47.6% achieved ≥50% and ≥75% improvement in Psoriasis Area and Severity Index scores, respectively. Patients continuing apremilast 20 mg also demonstrated consistent, sustained improvements. The most common adverse events were diarrhoea, nausea, headache, upper respiratory tract infection and nasopharyngitis. No new safety concerns were observed long term. Conclusions: Apremilast led to sustained PsA efficacy up to 260 weeks and was well tolerated. Trial registration: ClinicalTrials.gov (http://clinicaltrials.gov ), NCT01307423.